Digital PID Temperature Controlled Laminator Test Kit Design and Production for Small & Medium Scale Photovoltaic Module Production - Osman CICEK (Gazi Üniversitesi Fen Bilimleri Dergisi, 2018)
In this study, laminator design and production are realized for small & medium scale photovoltaic (PV) module production. The reliability of the energy to be supplied by the PV modules and / or the system is possible by being durable against external conditions and long life. This can be ensured by the protection provided by industrially mandatory lamination techniques. For the aim of the study, first, the solid model of the system is created using the Solidworks® program and the system is simulated for optimum production conditions. After this step, the components of the designed system are identified and aluminium plates are produced in CNC and assembled on the chassis. The temperature control is provided by the PID controller while the desired thermal distribution for lamination of the PV module layers is provided by cartridge resistors. The upper aluminium sheet with flexible membrane for vacuum and / or pressure procedures required for the lamination of the PV module components is positioned on the slide rails. Following completion of the design and assembly, cell matrices are constructed by connecting solar cells in series and / or parallel, and the system is tested for industrial performance. As a result, the digital PID temperature-controlled laminator test kit for PV module production will provide insight into the lamination processes in existing technologies and ensure that students at undergraduate / graduate level have the necessary knowledge and experience.